Philosophies of full mouth rehabilitation: A systematic review of clinical studies - Meenakshi Thimmappa; Vanshree Katarya; Ishita Parekh (Wolters Kluwer Medknow Publications, 2021)
Aim: To systematically review the available literature on full mouth rehabilitation of the worn out dentition to help the clinician to choose a suitable philosophy to treat an individual Turner and Missirlian classification. Settings and Design: Systematic review following PRISMA guidelines. Materials and Methods: The electronic search engine explored for relevant published studies from the earliest available date, from January 1960 till October 2018. Search terms included were "full mouth rehabilitation OR occlusion OR philosophies of full mouth rehabilitation OR oral rehabilitation OR Pankey Mann Schuyler philosophy OR Hobo Twin stage OR Hobo Twin Table OR worn out dentition OR Turner and Missirlian classification". All collected studies were analyzed and a total of 54 articles and 2 hand searches were extracted, among which 32 articles were selected for the systematic review. Of these 32 articles, 8 were original research studies, 23 case reports and 1 study which comprised 3 case reports were incorporated. Hence, a total of 26 case reports were considered for this systematic review based on CAse REport guidelines. Statistical Analysis Used: Qualitative analyisis. Results: Among 26 case reports, 15 cases (57.69%) were treated by Pankey Mann Schuyler philosophy, 2 cases (7.69%) by Hobo twin table and 9 cases (34.61%) by Hobo twin stage philosophy. 21 out of 26 cases were introduced for category no. 1 (80.76%) and 4 cases for category no. 2 (15.38%) and only 1case presented for category no.3 (3.84%) of Turner and Missirlian classification. Conclusion: No philosophies are universally applicable. Although the most commonly used philosophy is Pankey Mann Schuyler. Hobo Twin stage philosophy is the second most commonly used followed by Hobo Twin table. Maximum patients with worn out dentition are grouped under category no.1 of Turner and Missirlian classification system. Maximum cases of this category are treated by Pankey Mann Schuyler's philosophy.